Causes of Time Overrun in Construction of Building Projects in Pakistan - Soomro, F. A.; Memon, M. J.; Chandio, A. F.; Sohu, S.; Soomro, R. (Engineering, Technology & Applied Science Research, 2019)
Time overrun in construction projects is a very serious issue in developed countries. The main object of this research is to find the main causes of time overrun in the construction of building project and its possible mitigation measures. Quantitative approach was adopted in this research to achieve object and RIW (relative importance weight) approach was used for collecting data. Financial issues faced by the contractor, contractor’s inexperience, weather impacts, late delivery of material, mistakes in design, shortage of skilled labor, incompetent subcontractor and mistakes in time estimation were identified as main causes of time overrun in construction projects and possible mitigation measures were also proposed from experts. This research will help in giving awareness to stakeholders to narrow down the factors of time overrun in construction projects in Pakistan.